Risk identification method for automotive styling design tasks based on an improved FAHP-VIKOR approach - Jiefeng Lyu; Ganshu Sheng; Zihao Wang (PLoS ONE, 2026)
To address the difficulty of quantifying risks in current automotive styling-design task management, this study proposes a risk identification method for automotive styling design tasks based on an improved FAHP-VIKOR approach. First, the work breakdown structure (WBS) is constructed based on the principle of task modularity, and the risk breakdown structure (RBS) is established through the analysis of factors influencing risk, thereby forming the WBS-RBS coupling matrix for automotive styling design. Then, the improved fuzzy analytic hierarchy process (FAHP) is employed to determine the weights of risk factors such as technical, schedule, and cost risks, while the VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) method is applied to perform comprehensive ranking that adapts to the multidimensional and dynamic characteristics of styling design risks, thereby enabling quantitative risk assessment and identification. Finally, the design tasks involved in the exterior styling concept-design phase of a certain sport utility vehicle (SUV) model are taken as a case study and compared with the single FAHP method, the FAHP-TOPSIS method and the FAHP-VIKOR method. The results indicate that the proposed approach can classify the 27 core design tasks into high, medium and low risks, and can effectively identifies high-risk nodes such as the front bumper surface, lidar surface, and rear bumper surface. Compared with the other methods, the proposed method produces more stable and reasonable risk identification results and can provide decision-making support for risk management and optimal resource allocation in automotive styling design projects.